Evaluation of the first open-access hepatitis B and safe injection online training course for health professionals in China. Issue 1 (December 2016) - Wang, Jing; Feng, Qiming; Tam, Andrew; Sun, Tong; Zhou, Peijing; So, Samuel
Abstract Background Despite the high prevalence of chronic hepatitis B virus (HBV) infection in China, HBV infection prevention and long-term care knowledge of health professionals is inadequate. To address this knowledge gap, we developed an open-access evidence-based online training course, "KnowHBV", to train health professionals on prevention of HBV transmission and safe injections. We conducted an evaluation of the course with health professionals in China to examine its effectiveness in improving knowledge and learner's satisfaction of the course. Methods Between July and December 2011, 1015 health professionals from selected hospitals and disease control institutions of Shandong province registered for the course and 932 (92 %) completed the three-module course. Participants' demographic information, pre- and post-course knowledge test results and learner's feedback were collected through the course website. Results Pre-course knowledge assessment confirmed gaps in HBV transmission routes, prevention and long-term care knowledge. Only 50.4 % of participants correctly identified all of the transmission routes of HBV, and only 40.7 % recognized all of the recommended tests to monitor chronically infected persons. The number of participants that answered all six multi-part multiple-choice knowledge questions correctly increased from 183 (19.7 %) before taking the course to 395 (42.4 %) on their first attempt upon completion of the course. Over 90 % of the 898 participants who completed the learner-feedback questionnaire rated the course as 'good' or 'very good'; over 94 % found the course instructional design helpful; 57.5 %, 65.7 % and 68.5 % reported that half or more than half of the course content in modules 1, 2 and 3 respectively provided new information; and 93.2 % of the participants indicated they preferred the online learning over traditional face-to-face classroom learning. Conclusions The "KnowHBV" online training course appears to be an effective online training tool to improve HBV prevention and care knowledge of the health professionals in China.